Design of highly selective ultra-wideband (UWB) bandpass filter using step impedance resonator and parallel coupled lines - Khalid, S. (Institute of Electrical and Electronics Engineers Inc., 2015)
In this paper, a compact highly selective UWB bandpass filter is designed. The detailed analysis is provided for the design procedure where, Chebyshev type filtering response is extracted using even-odd mode analysis. The presented UWB bandpass filter consists of two 90o parallel coupled lines attached to a 270o step impedance resonator (SIR). In this configuration, six transmission poles are achieved in the passband. The step impedance resonator provides compactness as well as suppression of spurious resonance at high-frequency side. To validate the proposed design, a microstrip based fabrication is done on Roger Duroid 5880. The simulated and measured results are well correlated. Â© 2015 IEEE.